Manajemen Strategi Pengelolaan Taman Bacaan Masyarakat di Wadas Kelir - Dedah Jubaedah; Subur Subur (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Taman Bacaan Masyarakat (TBM) disediakan untuk memotivasi keminatan membaca bagi warga belajar dan masyarakat. Tujuan penelitian ini untuk mengetahui bagaimana manajemen strategi pengelolaan taman bacaan masyarakat di wadas kelir Kecamatan Purwokerto Selatan Kabupaten Banyumas. Jenis penelitian ini adalah field research atau penelitian lapangan dengan pendekatan kualitatif. Hasil penelitian mengungkapkan bahwa manajemen strategi pengelolaan mengacu pada tiga kategori yaitu, identifikasi strategi pengelolaan taman bacaan masyarakat, implementasi strategi pengelolaan taman bacaan masyarakatdan dampak strategi pengelolaan taman bacaan masyarakat. TBM Wades Kelir bergerak bersama warga masyarakat memprogram kegiatan peminjaman buku bacaan, ruang bacaan, ruang diskusi, sekolah literasi dan kegiatan sosial lainnya sehingga prestasi anak dan jenjang pendidikan bisa meningkat, dan banyak karya nyata. Community Reading Park (TBM) is a place for community learning with facilities for borrowing and borrowing books equipped with a discussion room, writing and other literacy activities. TBM provides reading materials that have been provided to motivate reading interest for learning residents and the community. The purpose of this study was to find out how the management strategy of the Community Reading Park in Wadas Kelir, South Purwokerto District, Banyumas Regency was managed. This type of research is field research or field research with a qualitative approach because it describes events or phenomena that occur. Field data collection was carried out using observation, interview and documentation techniques. Meanwhile, data analysis was carried out through data reduction, data display and conclusion drawing. The results of the study revealed that management strategy management refers to three categories, namely, identification of community reading park management strategies, implementation of community reading park management strategies, and the impact of community reading park management strategies. TBM Wadas Kelir works with community members in breaking the education chain, namely by programming reading book lending activities, discussion rooms, literacy schools, and other social activities. As a result, childrens achievement increases, education levels increase, and there are many real works.